DESENVOLVIMENTO, MATURAÇÃO E GERMINAÇÃO IN VITRO DE SEMENTES, E EMBRIOGÊNISE SOMÁTICA DE Euterpe edulis MARTIUS - Mello, Tamyris de (2022)
The species Euterpe edulis Martius, is a palm belonging to the Arecaceae family, popularly known as juçara, it is widely distributed in the Atlantic Forest. In recent decades this palm tree has been exploited for its palm heart, and the fact that it grows